Traditional Chinese medicine reimbursement reform in China: implementation progress, policy constraints, and optimization strategies - Fazheng Zhao; Yichi Chen; Xin Tong (Frontiers in Public Health, 2026)
Introduction As the inheritance, innovation, and development of TCM advance, medical insurance reimbursement policies are intended to improve access, guide service structure, and support high-quality development. This study examines the implementation progress, policy constraints, and optimization paths of TCM reimbursement reform in China. Methods The study analyzes publicly available national and regional policy documents, together with secondary literature, to synthesize the policy design, implementation arrangements, and evidence boundaries of TCM reimbursement reform. Results The policy corpus suggests that national and local governments have progressively expanded insurance support for eligible TCM institutions, techniques, and decocted herbal medicines, creating institutional conditions for broader reimbursement arrangements. At the implementation level, some regions have explored TCM outpatient syndrome-differentiation fees, DRG-based incentives, and outpatient global-budget management. However, current payment rules still do not fully align with TCM diagnostic and treatment characteristics. Key issues include incomplete recognition of syndrome differentiation and treatment value under DRG payment, low TCM service prices, insufficient reimbursement levels, static control of TCM decoction pieces costs, tension between zero-markup policies and payment reform, and immature quality-evaluation mechanisms under centralized procurement. Conclusion Based on these findings, the study proposes refining TCM-specific payment and pricing mechanisms, adjusting disease grouping and payment rules, dynamically revising cost-control standards, coordinating markup reform with compensation policies, and developing quality grading and “higher quality, higher price” mechanisms for herbal materials. Because the evidence is primarily policy-level, the study identifies policy instruments and implementation pathways rather than causal effects on service utilization, patient access, fund expenditure, or clinical outcomes.